Human bocavirus 1 is a genuine pathogen for acute respiratory tract infection in pediatric patients determined by nucleic acid, antigen, and serology tests - De, Ri; Zhang, Ke-Xiang; Wang, Fang; Zhou, Yu-Tong; Sun, Yu; Chen, Dong-Mei; Zhu, Ru-Nan; Guo, Qi; Liu, Shuang; Qu, Dong; Qian, Yuan; Zhao, Lin-Qing (Frontiers in Microbiology, 2022)
Background. Human bocavirus 1 (HBoV1), first discovered in 2005, was positive in symptomatic and healthy children and co-detected with other respiratory viruses. It is a long journey to decisively demonstrate the unique viral pathogenic function for acute respiratory tract infection (ARTI) in pediatric patients. Methods. Respiratory specimens collected from pediatric patients with ARTI from Jan 2017 to December 2021 were screened by a multiplex PCR-CEMP assay, then genotyped by PCR and sequencing for HBoV1. For antigen test, a part of HBoV1 DNA positive nasopharyngeal aspirates (NPAs) was used as antigens, while a rabbit anti-HBoV1 DR2 specific to HBoV1 was used as an antibody in the indirect-immunofluorescence assay (IFA). Finally, the levels of IgG specific to HBoV1 in acute and convalescent sera selected retrospectively from only HBoV1 DNA-positive patients were evaluated by IFA. Results. Among 9,899 specimens, 681 were positive for HBoV1 DNA (6.88%, 681/9899), which included 336 positives only for HBoV1 (49.34%, 336/681), and 345 (50.66%, 345/681) positives also for other pathogens. In the antigen test, there were 37 among 47 NPAs determined as HBoV1 antigen-positive (78.72%, 37/47), including 18 (48.65%, 18/37) positives solely for HBoV1 DNA. Among 4 pediatric patients with both acute and convalescent sera, there was one positive for HBoV1 antigen (D8873) and 2 lack the antigen results (D1474, D10792) who showed seroconversion with a  fourfold increase in IgG levels. Conclusions. The combination results of nucleic acid, antigen, and serology tests answered that HBoV1 is a genuine pathogen for ARTI in pediatric patients.